Estimation of social cohesion in the Spanish municipalities after the implantation of the high speed railway - José Antonio Gutiérrez Gallego; J. M. Naranjo Gómez; Francisco Javier Jaraíz Cabanillas; Enrique Eugenio Ruiz Labrador (Boletín de la Asociación de Geógrafos Españoles)
Texto resumen.